Galileo-E6 Bandwidth Frequency Filter Design for Galileo Receiver - Surachet Chinnapark; Narumol Onanong; Julongkorn Pattameak; Teerachet Mekpradab; Prasert Kenpankho (Universitas Pendidikan Indonesia (UPI), 2021)
This research discusses about the combination of the LPF and HPF to perform band reject filter. Therefore, there are two combination also in designing band reject filter. The aim of this combination to get know is there have an influence on the performance of band reject filter was designed by using the frequency of the GalileoE6 with bandwidth 40 MHz. This filter is used a Butterworth filter which is presented in this study. These filter circuit is composed 4rd order. In addition to, the combination between LPF and HPF forming to a band reject filter is designed. As a result, the filter design on the frequency of Galileo-E6 is successfully used in band reject filter.